Risk of Diabetes Mellitus in Carotid Artery Involvement Among Coronary Artery Disease Patients Including History of Infection and Antibiotics Uses - Rahman, AKM Mustafizur; Sharmin, Farzana; Haque, Mujammel; Khan, Kaspia; Karim, Mohammad Nazmul (Bangladesh Journal of Medical Microbiology, 2023)
Background: Diabetes mellitus causes involvement of coronary artery diseases. Objective: The purpose of the present study was to determine the risk of diabetes mellitus in the involvement of carotid artery among coronary artery disease patients. Methodology: This case-control study was conducted in the Department of Cardiology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July 2013 to June 2015 for a period of two years. Patients who had coronary artery diseases or ischemic heart diseases and diabetes mellitus undergoing coronary angiography were selected as case of this study. In control group, age, sex match patients of IHD undergoing CAG not having DM were included. Every patient was clinically examined by detailed history and physical examination during entry into study. ECG, chest X-ray, echocardiogram, blood sugar (fasting), blood 2 hrs. after 75 gm of glucose and or breakfast were analyzed. Coronary angiography was done in all patients through femoral approach by modified Seldinger technique. Carotid arteriography was performed selective and nonselective method by Hunter head or right Judkin's catheter in standard AP, lateral and oblique views. Results: A total number of 100 patients were included in this study. Of them 50 patients were coronary artery disease with diabetes mellitus and another 50 patients were coronary artery disease without diabetes mellitus. The mean height of the DM was 163.4±8.5 cm and in NDM was 160.6±7.1 cm, mean weight of DM 63.5±7.2 kg, in NDM was 62.0±15.4 kg and mean BMI in DM was 26.24±2.36 kg/m2 and in NDM was 26.38±2.05 kg/m2. The mean total cholesterol in DM was 236.9±34.1 mg/dL and in NDM was 208.0±36.4 mg/dL, mean serum TG in DM 240.5±76.3 mg/dl and in NDM was 207.6±57.8 mg/dl and mean serum IDL in DM was 166.1±130.6 mg/dL and in NDM was 142.8±30.4 mg/dL, no significant mean difference was observed between DM and NDM in height, weight and BMI (P>0.05). Concussion: In conclusion, significant mean difference is observed between DM and NDM in total cholesterol, serum triglycerides. Bangladesh Journal of Medical Microbiology, July 2023;17 (2):82-87